Filipina Domestic Workers as Contemporary Working-Class Poets: Writing as a Transformative Force - Zhang, Luka Lei (Archīum Ateneo, 2024)
In recent years, there has been a surge in the publication of poetry collections written by Filipina domestic workers across various locations, including Singapore, Malaysia, and Hong Kong. Notably, these poets have elected to publish their work through small independent presses, such as Poetry Planet Book Publishing House in the Philippines, rather than the more prevalent trend of migrant worker writings appearing in literary competitions and anthologies. The emergence of these poetry collections represents a unique and timely literary and cultural landscape that merits academic attention. This paper begins by contextualizing them as part of contemporary working-class literature and introducing the broader cultural formations that have catalyzed the rise of single-authored poetry publications by Filipina domestic workers. Specifically, the article delves into the published works of four Filipino worker poets: Rolinda Onates Española, Ailenemae Ramos, Joan Santillan Amurao, and Janelyn Dupingay. By analyzing their poems across two key sections, the work argues that their writing serves as a transformative force in two crucial ways: 1) as a means of (re)claiming agency, dignity, and a form of “remaindered life-times” for the poets themselves; and 2) as a collaborative endeavor to foster solidarity and empowerment within migrant worker communities, challenging prevailing class and gender hierarchies in both social and literary spheres. Through these poetic interventions, these writers transcend the conventional narratives typically ascribed to domestic workers, and instead, construct a distinctive literary articulation of their artistic expressions, and collective alliances. By placing these female migrant workers’ writings within the tradition of working- class literature, this paper expands the parameters of that canon to include the perspectives of those workers in the Global South who have historically been excluded from its purview.